Primary School Teacher’s Awareness and Knowledge of Dyslexia in Qassim Region-Saudi Arabia - Alharbi Hatim Yousef, (Pakistan Journal of Medical & Health Sciences, 2022)
Dyslexia represents a major educational and medical issue. Students with dyslexia can go through multiple psychological and emotional problems such as depression and anxiety. Primary school teachers could play a crucial role in identifying dyslexia early and creating awareness about learning disorders in the community. However, there are very few studies on the knowledge of primary school teachers about dyslexia. This study aims to assess the knowledge and awareness of dyslexia in primary school teachers in Qassim region-Saudi Arabia and to assess the variables influencing the knowledge. Therefore172, teachers from different primary schools in the Qassim region were given a self-report questionnaire, socio-demographic history was elicited, and the teacher’s preparation and knowledge were assessed based on their responses to the questionnaire. The results showed that most teachers lack the training, knowledge, and skills to diagnose dyslexic students in their classrooms. Furthermore, the higher levels of knowledge and awareness were significantly correlated with higher educational level, being a teacher for the lower classes, and working as a special education teacher. The findings of this article carry the notion that the lack of knowledge and awareness among school teachers regarding the term dyslexia puts the affected students at significant difficulties.